Successful Treatment of Necrotizing Fasciitis and Streptococcal Toxic Shock Syndrome with the Addition of Linezolid - Rac, Hana (Case Rep Infect Dis, 2017)
Necrotizing fasciitis is a deep-seated subcutaneous tissue infection that is commonly associated with streptococcal toxic shock syndrome (TSS). Surgical debridement plus penicillin and clindamycin are the current standard of care. We report a case of necrotizing fasciitis and streptococcal TSS where linezolid was added after a failure to improve with standard therapy. Briefly after isolation of Streptococcus pyogenes from tissue cultures, the patient underwent two surgical debridement procedures and was changed to standard of care therapy. While the patient was hemodynamically stable, the patient's wounds, leukocytosis, and thrombocytopenia all progressively worsened. After initiation of linezolid, the patient slowly improved clinically. The present report is the first to highlight the role of linezolid in streptococcal necrotizing fasciitis and TSS not improving with standard therapy.